Role of POCUS in Assessing an Acute Aortic Thrombus - Zachary Boivin; Emily Mensel; Trent She (CINQUILL Medical Publishers Inc., 2023)
A 67-year-old female patient presented with abdominal pain with a recent diagnosis of paroxysmal atrial fibrillation. Computed tomography (CT) of the abdomen demonstrated a filling defect concerning for an aortic thrombus. Point of care ultrasound (POCUS) confirmed a mobile thrombus in the proximal abdominal aorta in close proximity to several major arterial branches, leading to urgent surgical consultation due to a concern for mesenteric and end-organ ischemia. POCUS played a role in determining patient management in this novel case, and the patient was anticoagulated and ultimately discharged from the hospital.